EFFECT OF CROSSLINKING TO THE MECHANICAL PROPERTY OF APATITE GELATIN HYBRID FOR BONE SUBSTITUTION PURPOSES - Sunarso Sunarso; Sutarno Sutarno; Kanji Tsuru; Ika Dewi Ana; Kunio Ishikawa (Universitas Gadjah Mada, 2011)
The clinical success of current generation of synthetic bone substitute relies on bio-inspired design which has a performance level close to that of natural one. In this context, biomedical approaches are considered very important to result bio-functional hybrid for bone substitution purposes. In this study, effect of cross-linking to the mechanical properties of apatite gelatin hybrid has been investigated. Cross-linking was employed by 1-ethyl-3-3-dimethylaminopropyl carbodiimide (EDC) agent. The EDC agent creates a peptide bond between gelatin molecules inside the hybrid to the cross-linked structure. Cross-linked structure of gelatin increases physical property of the hybrid since it can hold the outer forces longer than that of without cross-linking.